Differences in Soft-Sediment Infaunal Communities Between Shorelines with and Without Seawalls - Critchley, Lincoln P.; Bishop, Melanie J. (Estuaries and coasts, 2019)
Seawalls are an increasingly conspicuous component of coastlines, which may modify ecological communities through their effects on physical and biological processes. Effects of seawalls on ecological communities may vary spatially according to environmental conditions at the site of seawall placement, the local species pool, and the characteristics of the seawall itself. In the Austral Spring of 2014, we assessed how differences in infaunal communities between paired sedimentary sites with and without seawalls vary with tidal elevation and environmental conditions (i.e. sediment variables, benthic cover), at five locations within Brisbane Waters, New South Wales, Australia. Contrary to the prediction that differences in infaunal communities between sites with and without seawalls would be greatest at high intertidal elevation at which seawalls are built, we found greater differences at mid intertidal elevations. At muddy locations, characterised by high faunal abundance and richness, the abundance of mid intertidal infauna was less at sites with than without seawalls. By contrast, at sandy locations, which were characterised by low infaunal abundance and richness, the reverse pattern was seen. Although the structure of infaunal communities was correlated with sediment characteristics, sites with and without seawalls did not display consistent patterns of difference in sediment grain size or organic carbon content across locations. The greater difference in infaunal communities between sites with and without seawalls at mid than high or low intertidal elevations likely reflects an interaction between the proximity of habitat to seawalls and biological traits of the resident infaunal species that influence their susceptibility to perturbation.